Strategi Pemasaran Digital Ngetekwan Pempek: Studi Kualitatif Mengenai Dampak dan Efektivitasnya - Hananto, Djoko; Ferdiansyah, Muhammad Yuda; Zulfa, Apriliana Nadilah; Septyarulloh, Israfnu; Fatimah, Andien Rezahara Ayu; Mu’az, Khadlan; Irawan, Andika (EL-EMIR Institute, 2024)
This research aims to analyze the digital marketing strategy of Ngetekwan-Pempek Products and to identify key factors that contribute to the success of digital marketing campaigns and examine the challenges and opportunities faced by Ngetekwan-Pempek in implementing digital marketing strategies. This research uses a qualitative descriptive approach. We carried out this research using the main approach, namely library research. On the other hand, the literature study method is used to collect, search and analyze relevant literature such as books, journals, and organize sources from articles and previous research reports. Based on data analysis and discussion, conclusions can be drawn from research regarding the digital marketing strategy of Ngetekwan-empek empek that: First, digital marketing strategies in this day and age are good and really help Ngetekwan-Pempek in terms of marketing because in this digital era it can help to increase sales figures through various platforms, one of which is Tiktok and other online food marketing. Second, implementing branding awareness in business development. Third, sales using Market Places such as Gofood, Shopeefood can make sales and profits easier